2020
DOI: 10.1177/0300060520922339
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG12 promotes the proliferation, migration, and invasion of trophoblast cells by regulating the epithelial–mesenchymal transition and cell cycle

Abstract: Objective The deficient placental blood perfusion caused by the attenuated infiltration of trophoblast cells is a key factor in the occurrence of preeclampsia (PE). Furthermore, the long noncoding (lnc)RNA SNHG12 (small nucleolar RNA host gene 12) can promote the proliferation and metastasis of multiple tumor cells. However, whether lncRNA SNHG12 affects proliferation and metastasis of trophoblast cells is unclear. Methods We examined the level of lncRNA SNHG12 in plasma and placenta of patients with PE and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For example, lncRNA CCAT1 was highly expressed in PE, which could promote the progression of PE by inhibiting the expression of CDK4 (16). LncRNA SNHG12 promoted the transition of trophoblast cells from the G0/G1 phase to S phase, and then promoted the occurrence of PE (29). This study further showed that knockdown of LINC00922 significantly inhibited the expression of cell cycle-related proteins CDK2, Cyclin D1, and PCNA, and promoted the expression of p21, while overexpression of LINC00922 had the opposite effect.…”
Section: Discussionmentioning
confidence: 57%
“…For example, lncRNA CCAT1 was highly expressed in PE, which could promote the progression of PE by inhibiting the expression of CDK4 (16). LncRNA SNHG12 promoted the transition of trophoblast cells from the G0/G1 phase to S phase, and then promoted the occurrence of PE (29). This study further showed that knockdown of LINC00922 significantly inhibited the expression of cell cycle-related proteins CDK2, Cyclin D1, and PCNA, and promoted the expression of p21, while overexpression of LINC00922 had the opposite effect.…”
Section: Discussionmentioning
confidence: 57%
“…Knockdown of lncRNA CRNDE has been reported to inhibit the proliferation, migration, and invasion of HTR-8/SVneo cells, inhibit the formation of EMT, and reduce the protein expression of MMP2 and MMP9 [31]. Zhou et al reported that lncRNA SNHG12 promoted trophoblast cell migration and invasion by inducing the progression of EMT [32]. Consistent with their study, we found knockdown of lncRNA BC030099 elevated MMP2, MMP9, and snail levels and repressed E-cadherin level.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively lncRNAs can directly interact with other chromatin modifiers to recruit or deflect their action on transcription (49,50). One lncRNA worth mentioning here, Snhg12 , has been linked to regulation of the cell cycle and promotion of the Epithelial-Mesenchymal Transition in embryogenesis (51). In addition, Snhg12 has been shown to promote cell proliferation and inhibit apoptosis in multiple cancers (52), including testosterone-sensitive prostate cancer (53).…”
Section: Resultsmentioning
confidence: 99%